Software reconocedor de placas para el control de vehículos en la Universidad Nacional de Trujillo - Coaquera Ponce, Alfredo Junior (2022)
The objective of this research is to determine the influence of the license plate _x000D_ recognition software in the control of vehicles at the National University of Trujillo, also the _x000D_ research is quantitative applied type and the applied design was pre-test and post-test _x000D_ contrastation, the study population was the vehicle controls, with a simple random sample _x000D_ type of proportions, The sample size was 384 objects of study, for data collection the _x000D_ observation technique was used and as an instrument observation guides were used, for _x000D_ the contrasting of hypotheses, the Mann Whitney U non-parametric statistical test was _x000D_ applied, which resulted in an asymptotic significance of 0.000, which proved that the use _x000D_ of the software had a significant influence on the control of University vehicles